2020
DOI: 10.1155/2020/3967414
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Integrated Therapeutic Methods in Noninvasive Lower Back Pain Therapy (LBP): The Role of Interdisciplinary Functional Diagnostics

Abstract: Introduction. Lower back pain (LBP) is almost a problem of civilizations. Quite often, it is a consequence of many years of disturbed distribution of tension within the human body caused by local conditions (injuries, hernias, stenoses, spondylolisthesis, cancer, etc.), global factors (postural defects, structural integration disorders, lifestyle, type of activity, etc.), or systemic diseases (connective tissue, inflammation, tumours, abdominal aneurysm, and kidney diseases, including urolithiasis, endometrios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 164 publications
(167 reference statements)
0
6
0
1
Order By: Relevance
“…e return to regular activity should be strictly supervised and based on an accurate diagnostic-rehabilitation plan [69,95]. e recommended treatment, as a component of fracture prophylaxis, mainly involves the initiation of pharmacological treatment, after prior bone density diagnosis and/or X-ray examination.…”
Section: Discussionmentioning
confidence: 99%
“…e return to regular activity should be strictly supervised and based on an accurate diagnostic-rehabilitation plan [69,95]. e recommended treatment, as a component of fracture prophylaxis, mainly involves the initiation of pharmacological treatment, after prior bone density diagnosis and/or X-ray examination.…”
Section: Discussionmentioning
confidence: 99%
“…71,[76][77][78][79][80][81] PNE combined with psychological interventions such as MBSR and CBT allows patients to understand and reframe their beliefs around pain and disability and as part of an interdisciplinary pain program, and has been shown to be highly effective. 80,82 A 2015 Cochrane review of RCTs including 41 trials and 6,858 patients demonstrated superiority of a multidisciplinary biopsychosocial model on chronic low back pain with respect to patient's pain and disability, compared with usual care and physical treatments only. 75 Interdisciplinary Endometriosis Care: The BC Women's Model There has been a call for development of centers of expertise on endometriosis.…”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…Non-specific low back pain (NSLBP) is a type of low back pain not attributable to a specific pathology (e.g., fracture, tumor, structural deformity, infection, an inflammatory disorder, osteoporosis, radicular syndrome, or cauda equina syndrome). When assessed using The International Classification of Functioning, Disability, and Health (ICF), problems that arise in non-specific LBP include pain, restriction/limited range of motion in rotation, extension, and flexion, as well as decreased functional ability in carrying out daily activities (Bitenc-Jasiejko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Disability, and Health (ICF), problems that arise in non-specific LBP include pain, restriction/limited range of motion in the lumbar region, as well as decreased functional ability to carry out daily activities(Bitenc-Jasiejko et al, 2020). Interventions for individuals with NSLBP should be combined with other therapeutic modalities such as manual therapy and training (stretching and muscle strengthening) to provide maximum effect…”
mentioning
confidence: 99%